PEMANFAATAN LIMBAH MAHKOTA NENAS UNTUK MENURUNKAN KADAR FOSFAT LIMBAH LAUNDRY SEBAGAI SUMBER BELAJAR KIMIA - praslita dishadewi; Pangaloan soleman ritonga (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2018)
AbstractThis research was instigated bythe emergence of environmental pollution problems caused by laundry waste.  The problem could be solved by processing the waste using the active carbon of pineapple crown, by utilizing adsorption properties found on Colloid material.  The research findings would be as the learning resource.  This research aimed at producing the valid and practical learning resource.  The learning resource product developed was such interactive multimedia using Lectora Inspire software.  This research was a Research and Development (R&D) with Define, Design, and Develop steps.  This research was administered at State Senior High Schools 1 and 2 Bangkinang Kota.  Validity and practicality test questionnaires were the instruments of collecting the data, and the data were analyzed by using descriptive qualitative and quantitative analysis techniques.  The research findings stated that the active carbon of pineapple crown contained 5% water content and iodine absorption was 482.334 mg/g.  The reduction of Phosphate content oflaundry waste after being processedwith the active carbon of pineapple crown was 40.7%.  The learning resource produced in the form of interactive multimedia contained 93.51% validity (very valid) and 87.57% practicality (very good).  Based the findings, it could be identified that the learning resource tested was proper and practical to be used as the learning resource. Keywords:  The Active Carbon of Pineapple Crown, Laundry Waste, Learning Resource, Interactive Multimedia of Lectora Inspire, Adsorption